General construction of minimal balanced repeated measurements designs in non-circular periods of k different sizes. Issue 2 (1st February 2023) - Abdullah, Muhammad; Rasheed, H. M. Kashif; Ahmed, Rashid
Abstract: Repeated measurements designs (RMDs) are most important and useful designs in research of various fields due to their economical property but residual or carry over effects are integral parts of these designs. To cope with these problems, balanced or strongly balanced RMDs should be used. In this manuscript Generators are developed to obtain balanced, strongly balanced and weakly balanced not circular repeated measurements designs (BRMDs, SBRMDs and WBRMDs) for k periods. This is an extension of Abdullah et al. (2019 ) where BRMDs and SBRMDs are constructed for one, two and three periods of different sizes. Efficiencies of these designs for direct and residual effects are also computed.